Komparasi Performa REST API Laravel 11 dan CodeIgniter 4 Menggunakan Metode Eksperimental - valentina, Putri Eka; Dede Handayani; Surya Rizky Maulana Ibrahim; Nanang, Nanang; Kusumah Putra, Faris Maulana (Unversitas Muhammadiyah Riau, 2026)
This study evaluates the performance of Laravel 11 and CodeIgniter 4 REST API frameworks using an experimental method with controlled variables. Both frameworks were built with identical CRUD endpoints and stress-tested using Apache JMeter 5.6 at concurrency levels of 100, 500, and 1,000 users, with 10 replications each. Key metrics were response time, throughput (RPS), and server memory usage. Results show CodeIgniter 4 consistently outperforms Laravel 11 in raw speed: 70 ms vs. 100 ms at 100 users; 310 ms vs. 480 ms at 1,000 users — a 35–55% advantage. Throughput ratio reached 2.09:1 in favor of CodeIgniter 4 (1,420 vs. 680 RPS at low load), while memory consumption was 66% lower (10 MB vs. 30 MB per request). Analysis of ORM impact shows Eloquent adds a 24% penalty over Query Builder (385 ms vs. 310 ms for 1,000-record fetches). However, applying route caching, config caching, and OPcache boosted Laravel 11 throughput by 75% (reaching 1,180 RPS) and narrowed response time to 85 ms. These findings provide empirical guidance: CodeIgniter 4 suits lightweight microservices with limited resources, while Laravel 11 is preferable for complex enterprise systems demanding security, maintainability, and team productivity.